Analisis Struktural dan Nilai-Nilai Pendidikan pada Novel Sagaras Karya Tere Liye Sebagai Bahan Ajar Pembelajaran Sastra di SMA - Khoirul Fajri; Muji Zain Naufal; Khodija Khodija (Departement of Mathematics Education, 2024)
The educational values in literary works offer advice to readers and often provide criticism, urging them to become better individuals. With the rise of juvenile delinquency, it is crucial to instill strong educational values in the younger generation. Literature education in the classroom aims to teach character education through life stories and characters that provide life views and lessons. This study examines the novel